Art Design of Ceramic Sculpture Based on 3D Printing Technology and Electrochemistry - Junxi Zhu; Weiyu Liu (Journal of Chemistry)
In order to solve the artistic design of ceramic sculpture, we proposed a method based on 3D printing technology for ceramic sculpture. First, using ANSYS ICEMCFD simulation software, we verified the effectiveness of the ceramic sculpture design method based on 3D printing technology in this study. Second, the design method of this study is recorded as the experimental group A. The two traditional design methods are recorded as experimental group B and experimental group C, respectively. Finally, we determined and compared the effect, size error, and precision error of the three groups of design methods to design the product. Ceramic sculptures are designed by proving the design method, high pattern definition, and small surface precision error. In the three directions of x-axis, y-axis, and z-axis, the relative size error generated is small, and the error is maintained below 1.0, and the effect of the finished product is consistent. So, the surface roughness of the ceramic sculpture designed this time is low, which will not affect the dimensional accuracy of the ceramic sculpture.